# Calculator search results

Formula
Solve the equation
Graph
$y = 3 \left ( x + 5 \right )$
$y = 7 x - 9$
$x$Intercept
$\left ( - 5 , 0 \right )$
$y$Intercept
$\left ( 0 , 15 \right )$
$x$Intercept
$\left ( \dfrac { 9 } { 7 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 9 \right )$
$3 \left( x+5 \right) = 7x-9$
$x = 6$
 Solve a solution to $x$
$\color{#FF6800}{ 3 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } \right ) = 7 x - 9$
 Multiply each term in parentheses by $3$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } = 7 x - 9$
$3 x + \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } = 7 x - 9$
 Multiply $3$ and $5$
$3 x + \color{#FF6800}{ 15 } = 7 x - 9$
$3 x + 15 = \color{#FF6800}{ 7 } \color{#FF6800}{ x } - 9$
 Move the variable to the left-hand side and change the symbol 
$3 x + 15 \color{#FF6800}{ - } \color{#FF6800}{ 7 } \color{#FF6800}{ x } = - 9$
$3 x \color{#FF6800}{ + } \color{#FF6800}{ 15 } - 7 x = - 9$
 Move the constant to the right side and change the sign 
$3 x - 7 x = - 9 \color{#FF6800}{ - } \color{#FF6800}{ 15 }$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 7 } \color{#FF6800}{ x } = - 9 - 15$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } = - 9 - 15$
$- 4 x = \color{#FF6800}{ - } \color{#FF6800}{ 9 } \color{#FF6800}{ - } \color{#FF6800}{ 15 }$
 Find the sum of the negative numbers 
$- 4 x = \color{#FF6800}{ - } \color{#FF6800}{ 24 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 24 }$
 Change the sign of both sides of the equation 
$4 x = 24$
$\color{#FF6800}{ 4 } \color{#FF6800}{ x } = \color{#FF6800}{ 24 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ 6 }$
 그래프 보기 
Graph
Solution search results